Balancing quality and quaternary care imperative using a high-risk case review committee in adults. (31st October 2022) - Ibrahim, Michael; Acker, Andrew; Weiss, Steve; Lawrence, Kendall; Ottemiller, Stephanie; McGarvey, Jeremy; Epler, Mark; Williams, Matthew; Szeto, Wilson Y; Acker, Michael
Abstract: OBJECTIVES: Quaternary care centres have an imperative to serve as hospitals of last resort and must also meet professional quality targets. We developed a high-risk committee (HRC) to evaluate cases meeting pre-defined predicted risk cut-offs as a part of an overall quality improvement drive. METHODS: We describe the structure, outcomes and effects of the Penn HRC. Using propensity-matching, we investigated whether the committee modifies or screens risk. We used multivariable analysis to examine the impact of unmeasured variables on clinical outcomes in this cohort. RESULTS: Institutional predicted and observed mortality had already been in decline prior to HRC institution in 2017, due to a multi-faceted quality improvement initiative. Between 2017 and 2020, the HRC discussed 205 patients with a median predicted risk of mortality of 10.6% (range 0.4–66%). Coronary artery bypass grafting was the most commonly presented operation. A total of 155 patients underwent operation (risk 10.3%), 12 had surgery deferred for optimization (risk 6%), 50 had surgery declined (risk 11.7%) and 12 patients had a deferred decision for further investigation. Overall 30-day survival was 86% for the entire cohort and 89% for operated patients. A matched analysis of similar patients prior to and following the HRC showed that the HRC did not directly modify outcomes. Most patients had better than expected survival (observed:expected mortality < 1). Predicted risk did not predict 30-day mortality among this high-risk cohort. CONCLUSIONS: HRCs serve as an important element in quality improvement by encouraging a thoughtful approach and channelling the collective experience of a group of senior surgeons. It may improve patient selection by identifying a cohort with extremely poor survival, while allowing safe operation with acceptable outcomes among a group with very high operative risk. Abstract : Quaternary academic medical institutions have an obligation to serve as hospitals of last resort and have considerable experience and resources which are of utility in the care of this challenging cohort [1–5].